Penggunaan Alat Peraga “Papan Pintar” untuk Meningkatkan Numerasi di Desa Wali Ate - Yuliana Tamu Ina Nuhamara; Elsy Senides Hana Taunu; Karolina Albina Rewa (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The lack of understanding of the concept of Multiplication and Division as well as the lack of knowledge about learning media or teaching aids for children in Wali ATE Village encouraged the Team to carry out socialization activities on the use of Smart Board teaching aids to improve numeracy skills, especially multiplication and division material. The implementation of the activity started with a demonstration of the use of smart board props by the Team, followed by the opportunity for the children to try out the smart board props. The results show that it is easier for children to understand the concept of multiplication and division of numbers as seen from the children's enthusiasm in playing the smart board props